Singular Perturbations and Large Time Delays Through Accelerated Spline-Based Compression Technique (Contemporary Mathematics, 2024)
In the quest to solve the singularly perturbed delay differential equations (SPDDEs) involving large delay with integral boundary condition, the cubic spline in compression technique is explored for the study of dynamical systems to capture complex temporal phenomena in a wide range of scientific disciplines. The integral boundary condition is handled using Simpson's 1/3 rule and the scheme's applicability is validated by numerically experimenting with some problems at different values of mesh size and perturbation parameter. Numerical data are tabulated to show that the suggested approach is more accurate and is an improvement over the methods used in the literature. The insights gained from this research paper provide a foundation for further exploration and utilization of SPDDEs in understanding and predicting the behavior of complex systems across diverse scientific domains.
Keywords: delay differential equations, singular perturbation problems, numerical methods, cubic spline in compression, integral boundary conditions, large delay, convection-diffusion problem